Investigation of the Effects of Porous Asphalt Mixtures Prepared with Different Modified Binders on the Performance Characteristics of Semi-Rigid Pavements - Akilli, Alev; Yalcin, Erkut; Yilmaz, Mehmet (Turkish Chamber Civil Engineers, 2025)
In this study, the effects of porous asphalt mixtures prepared with different aggregate types and modified binders on the performance of semi-rigid pavements were examined. Porous asphalt mixtures were created using limestone and basalt aggregates along with 50/70 and 160/220 penetration grade bitumen, as well as modified binders containing SBS (Styrene-Butadiene-Styrene) polymer and CR (Crumb Rubber) additives. In the first stage of the study, physical and mechanical tests were conducted on the aggregates, and binder tests were performed on the bitumen samples. In the second stage, modified binders were prepared in different ratios, the optimal modification percentages were determined, and porous asphalt mixtures were produced accordingly. In the third stage, semi-rigid pavement specimens were prepared by injecting suitable cement mortar into the voids within the porous asphalt mixtures, and performance tests were conducted. The results indicated that mixtures prepared with 6.5% CR and 3.5% SBS-modified binders exhibited improved performance characteristics, and for cement mortar mixtures, a water/cement ratio of 0.50 and the use of 2% superplasticizer additive yielded a high-strength and highly flowable cement mortar.
Keywords: Porous asphalt; semi-rigid pavement; limestone; basalt; SBS (Styrene-Butadiene-Styrene); CR (Crumb Rubber)